Empirical analysis of knowledge and adoption spectrum of recommended wheat (Triticum aestivum L.) agronomic practices among farming community - Avneesh Kumar; N.R. Meena; R.K. Doharey; Ranjeet Kumar; Sandeep; A.P. Verma; Amit Kumar (Annals of Agricultural Research, 2025)
Wheat is an important source of nutrition in our staple diet. Although farmers in northern India are growing wheat for a long time many farmers are lacking good knowledge of wheat and its new varieties production practices. The study was conducted during 2022-23 to know the extent of knowledge and adoption of recommended wheat production practices among wheat cultivating farmers of the Lakhimpur Kheri district of Uttar Pradesh. The result revealed that more than half (53.3%) of the wheat growers had medium level of knowledge followed by 26.6 and 20.0 percent had low and high level of knowledge respectively. Majority of the respondents (55.8%) had medium level of adoption followed by 32.5 percent low and 11.6 percent had high level of adoption respectively. Correlation analysis revealed that out of sixteen variables i.e., age, caste, education, material possession, risk orientation, scientific motivation, extension contact, was found highly significant and positively correlated with knowledge level.